Media Representation of the Online Gambling Phenomenon in Indonesia through a Corpus-Assisted Critical Discourse Study - Raden Yusuf Sidiq Budiawan; Rawinda Fitrotul Mualafina; Siti Ulfiyani; Mukhlis Mukhlis (Indonesian Language Education and Literature, 2025)
This study aims to describe media representation of the phenomenon of online gambling in Indonesia through a corpus-assisted critical discourse analysis approach, with a focus on news in Kompas.com. The method used is corpus-based critical discourse analysis, which allows systematic exploration of news data to identify language patterns that frame the issue of online gambling. The analysis was conducted on a news corpus containing 5613 words and 43042 tokens using the AntConc application. The results show that the words “gambling” and “online” have the highest frequency, signaling the main focus on this phenomenon. The dominant social actors are government officials, such as “Budi Arie,” who is portrayed positively as a pioneer in eradicating online gambling, while online gambling perpetrators are portrayed destructively. Victims are seen as suffering and in need of external intervention. The social actions represented highlight the government's efforts to eradicate online gambling, with word choices that emphasize the urgency of handling this problem. Kompas.com frames the issue of online gambling by strengthening the role of the government as a protector, the perpetrator as a public enemy, and the victim as a party that needs to be saved. This study implies that online mass media play an important role in shaping public discourse, emphasizing the legal and moral sides, and introducing various perspectives that frame this issue.Representasi Media terhadap Fenomena Perjudian Online di Indonesia melalui Kajian Wacana Kritis Berbantuan KorpusPenelitian ini bertujuan untuk mendeskripsikan representasi media terhadap fenomena perjudian online di Indonesia melalui pendekatan analisis wacana kritis berbantuan korpus, dengan fokus pada berita di Kompas.com. Metode yang digunakan adalah analisis wacana kritis berbasis korpus, yang memungkinkan eksplorasi sistematis data berita untuk mengidentifikasi pola bahasa yang membingkai masalah perjudian online. Analisis dilakukan pada korpus berita yang berisi 5613 kata dan 43042 token menggunakan aplikasi AntConc. Hasilnya menunjukkan bahwa kata "perjudian" dan "online" memiliki frekuensi tertinggi, menandakan fokus utama pada fenomena ini. Aktor sosial yang dominan adalah pejabat pemerintah.  Aksi sosial yang diwakili menyoroti upaya pemerintah untuk memberantas perjudian online, dengan pilihan kata yang menekankan urgensi penanganan masalah ini. Kompas.com membingkai isu judi online dengan memperkuat peran pemerintah sebagai pelindung, pelaku sebagai musuh publik, dan korban sebagai pihak yang perlu diselamatkan. Penelitian ini menyiratkan bahwa media massa online berperan penting dalam membentuk wacana publik, menekankan sisi hukum dan moral, serta memperkenalkan berbagai perspektif yang membingkai isu ini.